Altered expressions of endothelial junction protein of placental capillaries in premature infants with intraventricular hemorrhage (Medical Journal of Indonesia, 2016)
Background: Placental hypoxia may lead to oxidative stress, which inflicts damage to capillary protein junction. The aim of this study was to evaluate altered expression of endothelial junction protein of capillaries in hypoxia condition and to observe its correlation with the incidence ofÂ intraventricular hemorrhage in premature infants. Methods: A cross-sectional study was conducted by using placental tissues of premature infants as amodel of capillary integrity (29 hypoxic and 29 non-hypoxic). Hypoxia inducible factor (HIF)-1α was measured to define placental tissue response to hypoxia; malondialdehyde (MDA) and glutathione (GSH) served as markers of oxidative stress. The expressions of junctional proteins, N-cadherin and occludin were analyzed by immunohistochemistry. Intraventricular hemorrhage (IVH) was detected by cranial ultrasound at the third day. Unpaired t test, Mann-Whitney, and Chi-square tests were used to analyze the data. Results: The HIF-1α and MDA levels were slightly, but not significantly, higher in hypoxia group {13.64±8.70 pg/mg protein and 10.31 pmol/mg tissue (ranged 1.92–93.61), respectively} compared to non- hypoxia group {10.65±5.35 pg/mg protein and 9.77 pmol/mg tissue (ranged 2.42–93.31)}. GSH levels were not different in both groups (38.14 (ranged 9.44–118.91) and 38.47(ranged 16.49–126.76) ng/mg protein, respectively. mRNA expression of N-cadherin (0.13) and occludin (0.096) were significantly lower in hypoxia comparedto non-hypoxia group (p=0,001), while protein expression of N-cadherin (3.4; 75.9; 6.9; 13.8%) and occludin (20.7; 3.4; 69.0; 3.4; 6.9%) in hypoxia group was not associated with IVH (p=0.783 and p=0.743). Conclusion: Hypoxia altered expression of endothelial junction protein in placental capillaries, but no association with intraventricular hemorrhage was observed.